Improvement of ethanol production from crystalline cellulose via optimizing cellulase ratios in cellulolytic Saccharomyces cerevisiae. Issue 6 (6th March 2017) - Liu, Zhuo; Inokuma, Kentaro; Ho, Shih‐Hsin; den Haan, Riaan; van Zyl, Willem H.; Hasunuma, Tomohisa; Kondo, Akihiko
ABSTRACT: Crystalline cellulose is one of the major contributors to the recalcitrance of lignocellulose to degradation, necessitating high dosages of cellulase to digest, thereby impeding the economic feasibility of cellulosic biofuels. Several recombinant cellulolytic yeast strains have been developed to reduce the cost of enzyme addition, but few of these strains are able to efficiently degrade crystalline cellulose due to their low cellulolytic activities. Here, by combining the cellulase ratio optimization with a novel screening strategy, we successfully improved the cellulolytic activity of a Saccharomyces cerevisiae strain displaying four different synergistic cellulases on the cell surface. The optimized strain exhibited an ethanol yield from Avicel of 57% of the theoretical maximum, and a 60% increase of ethanol titer from rice straw. To our knowledge, this work is the first optimization of the degradation of crystalline cellulose by tuning the cellulase ratio in a cellulase cell‐surface display system. This work provides key insights in engineering the cellulase cocktail in a consolidated bioprocessing yeast strain. Biotechnol. Bioeng. 2017;114: 1201–1207. © 2017 Wiley Periodicals, Inc. Abstract : Through combining cocktail d‐integration method and a novel screening strategy using crystalline cellulose as substrate, the ratio of four synergistic cellulases in a cellulase‐displaying Saccharomyces cerevisiae was optimized. The ratio‐optimized yeast strain appeared significantly improved ethanol yield from Avicel (microcrystalline cellulose) and rice straw.